Allelic variation of MYB10 is the major force controlling natural variation in skin and flesh color in strawberry (Fragaria spp.) fruit - Castillejo, Cristina; Waurich, Veronika; Wagner, Henning; Ramos, Rubén; Oiza, Nicolás; Muñoz, Pilar; Triviño, Juan C; Caruana, Julie; Liu, Zhongchi; Cobo, Nicolás; Hardigan, Michael A; Knapp, Steven J; et al. (My University, 2021)
Fruits of diploid and octoploid strawberry (Fragaria spp.) show substantial natural variation in both skin and flesh color due to distinct anthocyanin accumulation and distribution patterns. Expression of structural genes involved in anthocyanin biosynthesis is controlled by transcription factors such as bHLH, MYB and WD repeat proteins, among which the R2R3 MYB10 is the main activator in strawberry fruit. Here, we show that independent mutations in MYB10 are behind the natural fruit color variation observed in diploid woodland strawberry (F. vesca) and octoploid cultivated strawberry (F. × ananassa). Using a mapping-by sequencing approach, we identified a gypsy-transposon in MYB10 that truncates the protein and knocks out anthocyanin biosynthesis in a white-fruited F. vesca ecotype. Two additional loss-of-function mutations in MYB10 were identified among geographically diverse white-fruited F. vesca ecotypes. Color variation in octoploid Fragaria spp was further investigated by genetic and transcriptomic analyses, which revealed that FaMYB10-2, one of three MYB10 homoeologs identified, is the dominant homoeolog and regulates anthocyanin biosynthesis in developing fruit. Furthermore, independent mutations in MYB10-2 are the underlying cause of natural variation in fruit skin and flesh color in octoploid strawberry. A genome-wide association study in F. × ananassa and analysis in other octoploid populations identified two independent polymorphisms in FaMYB10-2 causing white skin. Flesh pigmentation was associated with the insertion of a CACTA-like transposon (FaEnSpm-2) in the MYB10-2 promoter and with enhanced MYB10 expression. Our findings suggest that cis-regulatory elements provided by FaEnSpm-2 are responsible for ectopic MYB10-2 expression and anthocyanin biosynthesis in strawberry fruit flesh. Our results show that MYB10 exerts a simple genetic control over strawberry skin and flesh color, making it a good target for molecular breeding.
Keywords: Fresas; Strawberry; MYB10; Color; Transcription Factor